Mobile vehicle tracker using rf (hardware) - Ting, P.H (University Malaysia Sarawak, UNIMAS., 2004)
In this project, available RF tracking methods should be known. By knowing each RF tracking methods utilizing different design and circuity, careful consideration need to be taken when choosing which method should be used. By completing the design of the RF tracking method, the mobile vehicle tracker could be built. The circuit selected during design stage is used.